2021
DOI: 10.1016/j.ajic.2020.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of disinfection procedures in a designated hospital for COVID-19

Abstract: Highlights Evaluation the quality of disinfection in hospital during COVID-19 pandemic Revealed the places easy to be ignored when performed disinfection procedures Routine disinfection could be helpful in preventing the HCWs from getting infected

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 28 publications
0
18
0
3
Order By: Relevance
“…Some authors have also reported the presence of SARS-CoV-2 strains in the wastewater generated from the isolation centers and nearby hospitals where COVID-19 patients are being managed (J. Wang et al, 2020 ; Ge et al, 2020 ; Feng et al, 2021 ; Chakraborty et al, 2021 ; Ahmed et al, 2021 ; Hong et al, 2021 ), while others studies reported the presence of SARS-CoV-2 RNA in water and wastewater collected from wastewater treatment plants ( Ahmed et al, 2020a ; La Rosa et al, 2020 ; Hasan et al, 2020 ; Haramoto et al, 2020 ; Mlejnkova et al, 2020 ; Peccia et al, 2020 ; Randazzo et al, 2020 ; Wang et al, 2020 ; Rimoldi et al, 2020 ; Medema et al, 2020 ; Hokajärvi et al, 2021 ; Chavarria-Miró et al, 2021 ; Kitamura et al, 2021 ; Saguti et al, 2021 ), which are of course do not necessarily indicate the infectivity of the virus ( Buonerba et al, 2021 ). However, few studies have reported the detection and isolation of infectious SARS-CoV-2 from different environmental samples such as wastewaters ( Bivins et al, 2020 ; Lee et al, 2020 ; Sala-Comorera et al, 2021 ).…”
Section: Life Cycle and Persistence Of Sars-cov-2 In Water-food- Environment Interactionsmentioning
confidence: 99%
“…Some authors have also reported the presence of SARS-CoV-2 strains in the wastewater generated from the isolation centers and nearby hospitals where COVID-19 patients are being managed (J. Wang et al, 2020 ; Ge et al, 2020 ; Feng et al, 2021 ; Chakraborty et al, 2021 ; Ahmed et al, 2021 ; Hong et al, 2021 ), while others studies reported the presence of SARS-CoV-2 RNA in water and wastewater collected from wastewater treatment plants ( Ahmed et al, 2020a ; La Rosa et al, 2020 ; Hasan et al, 2020 ; Haramoto et al, 2020 ; Mlejnkova et al, 2020 ; Peccia et al, 2020 ; Randazzo et al, 2020 ; Wang et al, 2020 ; Rimoldi et al, 2020 ; Medema et al, 2020 ; Hokajärvi et al, 2021 ; Chavarria-Miró et al, 2021 ; Kitamura et al, 2021 ; Saguti et al, 2021 ), which are of course do not necessarily indicate the infectivity of the virus ( Buonerba et al, 2021 ). However, few studies have reported the detection and isolation of infectious SARS-CoV-2 from different environmental samples such as wastewaters ( Bivins et al, 2020 ; Lee et al, 2020 ; Sala-Comorera et al, 2021 ).…”
Section: Life Cycle and Persistence Of Sars-cov-2 In Water-food- Environment Interactionsmentioning
confidence: 99%
“…5,6 Routine disinfection is widely utilized to efficiently disinfect contaminated air/surface and control transmission of airborne infectious disease in hospital. 5 Routine disinfection includes running air disinfection machines, direct ultraviolet radiation and wiping indoor surface with chlorine containing disinfectant. 6 The operation of HVAC is also essential for air disinfection to maintain a healthy and comfortable indoor environment.…”
Section: Evaluation Of Indoor Disinfection Technologies For Airborne Disease Control In Hospitalmentioning
confidence: 99%
“…Both of these two methods have been proven to be effective by experiments. 5,6 Previous studies indicated that wiping with disinfectant (containing chlorine) could produce a better disinfection performance than UV radiation. 6 The disinfection efficacy of UV devices is influenced by distance, object occlusion (e.g.…”
Section: Indoor Surface Disinfection In Hospitalmentioning
confidence: 99%
See 1 more Smart Citation
“…All hardware equipment and public activity spaces must be disinfected, including restaurants, classrooms, stadiums, buses, etc. [13,14]. In addition, the entry and exit of visitors outside the school must be strictly controlled, and non-school personnel must be prohibited from entering when necessary [11].…”
Section: Formulation Of Campus Epidemic Prevention Measuresmentioning
confidence: 99%